2019
DOI: 10.1055/s-0039-1697904
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Lymphatic Transport Abnormalities in Patients with Primary Lipedema

Abstract: Background Although lipedema is often clinically distinguished from lymphedema, there is considerable overlap between the two entities. The purpose of this study was to evaluate lymphoscintigraphic findings in patients with lipedema to better characterize lymphatic flow in this patient population. Methods Patients with lipedema receiving lymphoscintigraphy between January 2015 and October 2017 were included. Patient demographics, clinical characteristics, and lymphoscintigraphic findings were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 27 publications
1
39
0
5
Order By: Relevance
“…The vascular changes in microcirculation, especially lymphatic vessels, suggest lymphostasis [4,5,8,15]. A study involving lymphoscintigraphy demonstrated lymphatic alterations in lipedema, suggesting lymphedema resulting from the lymphatic microcirculation [15]. The treatment of these patients using lymphatic drainage results in a reduction of the symptoms and circumference of the limb, which confirms the existence of the lymphatic component [9].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The vascular changes in microcirculation, especially lymphatic vessels, suggest lymphostasis [4,5,8,15]. A study involving lymphoscintigraphy demonstrated lymphatic alterations in lipedema, suggesting lymphedema resulting from the lymphatic microcirculation [15]. The treatment of these patients using lymphatic drainage results in a reduction of the symptoms and circumference of the limb, which confirms the existence of the lymphatic component [9].…”
Section: Discussionmentioning
confidence: 96%
“…The vascular changes in microcirculation, especially lymphatic vessels, suggest lymphostasis [4,5,8,15]. A study involving lymphoscintigraphy demonstrated lymphatic alterations in lipedema, suggesting lymphedema resulting from the lymphatic microcirculation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Lipedema, another subcutaneous adipose tissue disorder with excessive fat deposition under skin, exhibits lymphatic vessel microaneurysms causing leakage of lipids from damaged and leaky lymphatic vessels causing excessive adipogenesis (Stallworth et al, 1974;Herbst, 2000;Amann-Vesti et al, 2001;Al-Ghadban et al, 2019). Reports indicate that lymphatic transport defects are more prominent in late stage lipedema compared to early stages (Gould et al, 2020). In similar lines, research indicates that lymphedema a chronic, morbid disease characterized by tissue swelling, accumulation of fluids, fibro-adipose tissue spontaneously develops in severely obese individuals.…”
Section: Obesity Causes Lymphatic Dysfunction and Increases Risk Of Lmentioning
confidence: 99%
“…Ödeme sind bekanntlich definiert als "abnorme Flüssigkeitsansammlung" im Gewebe [34]. Bisher konnten allerdings weder klinische Untersuchungen noch Bildgebungen jemals ein relevantes Ödem bei Patientinnen mit Lipödem-Syndrom nachweisen [7].…”
Section: Zuunclassified